“To fast or not to fast?” Ramadan and religiosity through the eyes of people with bipolar disorder: an exploratory study - Mejri, Imen; Ouali, Uta; Gronholm, Petra C.; Zgueb, Yosra; Ouertani, Abdelhafidh; Nacef, Fethi (Frontiers in Psychiatry, 2023)
The month of Ramadan, due to its changes in social rhythms, can seriously affect the course of bipolar disorder (BD). Therefore, psychiatrists sometimes find it necessary to discourage Ramadan practices, especially fasting, although taking part in this practice can give a sense of belonging and accomplishment to patients. Research on this subject is limited. The aim of the present work was to explore: (i) religious practices with special attention to Ramadan before and after the onset of BD, (ii) the perceptions and behaviours related to not fasting during Ramadan in patients with BD and their families' attitudes, (iii) religiosity and self-stigmatization and their relationships with religious practices, and (iv) the doctor-patient relationship around fasting. Methods: We conducted a retrospective, cross-sectional and descriptive study in clinically stabilized patients with BD in a public mental hospital and in a private psychiatric practice in Tunis, Tunisia. Socio-demographic and clinical data, as well as data related to general religious practices and Ramadan practices were collected using a self-established questionnaire. We assessed (i) religiosity of the patients with the Duke University Religion Index and (ii) selfstigma using the Internalized Stigma of Mental Illness scale. Results: Our sample consisted of 118 patients of whom 65.3% were fasting regularly before BD onset. More than half had stopped this practice following BD onset. Of the patients who did not fast, 16% felt badly guilty about this and 4.9% reported receiving negative remarks from their surroundings. High self-stigma scores were observed in 11% of the patients. Self-stigma was associated significantly with negative perception of not fasting, negative remarks regarding not fasting and taking both meals at regular times during Ramadan. The decision whether to fast or not was taken without seeking medical advice in 71.2% of the sample, and 16.9% of the sample reported that their psychiatrist had spontaneously approached the issue of Ramadan fasting.